2014
DOI: 10.1111/apt.12633
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Helicobacter pylori eradication and age are independent risk factors for recurrent neoplasia after endoscopic resection of early gastric cancer in 283 patients

Abstract: SUMMARY BackgroundWhether the incidence of metachronous gastric dysplasia and cancer could be decreased by eradication of Helicobacter pylori after endoscopic submucosal dissection (ESD) for early gastric cancer (EGC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 34 publications
2
58
2
1
Order By: Relevance
“…In this regard, a prospective validation study would be mandatory in the future. Third, the metachronous cancer incidence rate was slightly high compared with that in past reports . This may be attributable to the high frequency of severe atrophy in our subjects.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In this regard, a prospective validation study would be mandatory in the future. Third, the metachronous cancer incidence rate was slightly high compared with that in past reports . This may be attributable to the high frequency of severe atrophy in our subjects.…”
Section: Discussioncontrasting
confidence: 58%
“…Aging has been reported to be associated with both occurrence of primary gastric cancer and metachronous recurrence, possibly because a long duration of HP infection is required for the development of gastric cancer. However, this factor was not significant in our study, probably as a result of the relatively older ages of our subjects compared to patients in studies showing age as a significant factor . Older age appears to be naturally correlated with high frequencies of severe atrophy and IM in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike surgery of EGC, ER preserves most part of the stomach and this leads to increased risk of metachronous gastric cancer (MGC) development in residual gastric mucosa[5]. As more EGCs are treated with ER recently, identifying risk factors of MGC development after ER of EGC is important.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 132 patients who underwent ER for EGC and showed positive H. pylori serologic test demonstrated that H. pylori eradication inhibited the growth of new gastric cancer[13] and a retrospective study of 283 patients with H. pylori infection at time of ESD for EGC showed that failure of H. pylori eradication was a risk factor of MGC development[5]. However, a study of 1258 patients who underwent ESD for EGC reported that the incidence rate of MGC was not significantly different between patients with or without H. pylori eradication[14] and a retrospective study of 268 patients with a 5-year follow-up reported that H. pylori eradication after ER for EGC did not significantly reduced the incidence of MGC[15].…”
Section: Introductionmentioning
confidence: 99%